PENGARUH KOMPOSISI DEDAK DAN TEPUNG JAGUNG PADA BAHAN MEDIA SERBUK GERGAJI TERHADAP PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Syawal, Muh.; Lasmini, Sri Anjar; Ramli, Ramli (AGROTEKBIS, 2018)
The research implemented in Mpanau Village, Sigi Biromaru, Sigi Regency. The study began from March to May 2016. The purpose of this research is to know the effect dosage of bran and corn flour on sawdust media to growth and yield of white oyster mushroom (Pleurotus ostreatus). The benefits of this research isa source of basic scientific provides information the growth and yield of white oyster mushrooms to the dosage of bran and corn flour as source of nutritious white oyster mushroom plant, In addition it is expected to be a reference for future researchers about mushrooms white oyster. The method of this study was arranged in the design of this the study using Completely Randomized Design (RAL) with 7 treatments as follows: D0 =  media sawdust (100%), as control, D1 = sawdust (80%), and bran (20%), D2 = mixture of sawdust media (75%), and bran (25%), D3 = mixed sawdust (70%), and bran (30%), D4 = mixture of sawdust (80%), and corn powder (20%), D5 = mixture of sawdust media (75%) and corn powder (25%), D6 = mixed sawdust (70%), and corn power (30%). The results of this study showed that the addition of dosage of bran and corn powder to each treatment of sawdust media had a very significant effect on all parameters of observation that is on the first observation parameter growing mycelium, the number of white oyster mushroom body, white fruits oyster mushroom cap dry weight of white oyster mushrooms. Treatment with 30% dosage of bran dose gave the best result to all observation parameters except on observation parameter of white oyster mushroom diameter. On the average parameter of white oyster mushroom fruits diameter the best treatment was treatment (D1) with dosage 20% of bran. Treatment by using a dosage of corn powder gives a low yield on all observation parameter. Keywords: Oyster mushrooms, Sawdust